Effects of 1.5°C and 2°C of warming on regional reference evapotranspiration and drying: A case study of the Yellow River Basin, China. (15th June 2020) - Jian, Dongnan; Ma, Zhuguo; Chen, Liang; Duan, Jianping; Mitchell, Daniel; Zheng, Ziyan; Lv, Meixia; Zhang, Haoxin
Abstract: Reference evapotranspiration (ETo) is one of the most important factors influencing hydrologic and climatic quantities, and increases in ETo are often considered as a primary cause for drying under global warming scenarios. Based on bias‐corrected data from the Half a degree Additional Warming, Prognosis and Projected Impacts (HAPPI) experiment, we investigated changes in ETo and drying across the Yellow River Basin (YRB) for 1.5°C and 2°C stabilized warming, relative to the current decade (2006–2015). We used changes in the climatic water deficit (WD: defined as precipitation (P) minus (ETo) to determine drying and wetting trends. Results projected that mean annual ETo would increase significantly over the whole YRB, under 1.5°C and 2°C warming scenarios, with an increase of 4.54% (1.57–7.59% full uncertainty range) and 7.66% (4.49–10.61%), at 1.5°C and 2°C, respectively, averaged over the YRB for the multi‐model mean. It is unclear whether the YRB source region (the NE region of the Tibet Plateau) would be drier or wetter under 1.5°C and 2°C of warming, although it is likely that the N regions of the YRB, and the whole YRB except for the source region will be drier under 1.5°C and 2°C warming scenarios, respectively. With an additional 0.5°C warming, further intensification of drying is projected in the whole YRB, resulting from a more pronounced increase in ETo, and lesser increase/decrease in P. The increased ETo projected under a 0.5°C additional warming was mainly attributed to rising maximum temperatures (tasmax). These results highlight the importance of ETo, in terms of potential future YRB drying, and our study suggests that limiting future warming to 1.5°C would impact regional drying the least. Abstract : This study has investigated reference evapotranspiration (ETo) and drying changes across the Yellow River Basin (YRB) at 1.5 °C and 2 °C of warming. Results showed that ETo would increase significantly over the whole YRB at 1.5 °C and 2 °C relative to 2006–2015 period. The N regions of the YRB and the whole YRB except for the source region would be drier at 1.5 °C and 2°C, respectively. With an additional 0.5 °C warming, the whole YRB would experience further intensification of drying